Castration affects reproductive but not aggressive behavior in a cichlid fish - Almeida, Olinda (2014)
Gonads are the main source of sex steroids, which have been implicated in the regulation of sexually differentiated behavior, such as reproductive and aggressive displays. In the Mozambique tilapia (Oreochromis mossambicus) territorial males have higher androgen levels than non-territorials, express reproductive behavior and use a urine-borne pheromone to signal their social status towards conspecifics. Here we investigated the effects of gonadectomy on the circulating levels of androgens and cortisol, and on the expression of aggressive and reproductive behavior (nest building, courtship behavior, and nuptial coloration). Males were either castrated, urine bladder damaged, or sham-operated and visually exposed to a group of females during 8 consecutive days and subsequently to a male on day 9. The urine bladder damaged treatment was included in the experimental design because a full castration procedure in this species causes quite often damage to the urine bladder. Gonadectomy lowers dramatically the circulating levels of androgens measured at 4 and 8 days post-castration and abolishes the expression of nest building, courtship behavior and nuptial coloration, but has no effect on the expression of aggressive behavior. These results confirm the gonads as the main source of androgens in this species and show that androgens are necessary for the expression of reproductive behaviors. However, the expression of aggressive behavior seems to be decoupled from gonadal steroids, namely androgens, suggesting the action of independent central mechanisms.